KRITIK AKAL DAN HISTORIS DALAM PEMIKIRAN MOHAMMED ARKOUN: TONGGAK FILSAFAT ISLAM MODERN - Fithri Choirunnisa Siregar; Riki Saputra; Rusydi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to explore Mohammed Arkoun's thought on the critique of reason and the dimension of historicity as the foundation of modern Islamic philosophy. Arkoun perceives that contemporary Islamic thought is trapped in a "dogmatic reason" that closes the space for new ijtihad. Using a qualitative-descriptive method through literature review, this article analyzes the three main pillars of Arkoun's methodology: deconstruction, the critique of Islamic reason (Critique de la raison islamique), and applied Islamology. The results show that Arkoun's critique of "the unthought" (l'impensé) and "the unthinkable" (l’impen-sable) successfully dismantles orthodoxies considered sacred but are, in fact, historical constructions. By integrating modern social sciences and humanities such as linguistics, semiotics, and anthropology, Arkoun offers a way for Muslims to reconcile tradition (turāth) with modernity. This study concludes that Arkoun's thought is not merely a destructive critique, but an epistemological milestone that allows for the reconstruction of a more inclusive, dynamic, and historical Islamic thought.